An Introduction to the Objective Psychophysics Toolbox - Hartmann, Thomas; Weisz, Nathan (Frontiers in Psychology, 2020)
The Psychophysics Toolbox (PTB) is one of the most popular toolboxes for the development of experimental paradigms. It is a very powerful library, providing low-level, platform independent access to the devices used in an experiment such as the graphics and the sound card. While this low-level design results in a high degree of flexibility and power, writing paradigms that interface the PTB directly might lead to code that is hard to read, maintain, reuse, and debug. Running an experiment in different facilities or organizations further requires it to work with various setups that differ in the availability of specialized hardware for response collection, triggering, and presentation of auditory stimuli. The Objective Psychophysics Toolbox (o_ptb) provides an intuitive, unified, and clear interface, built on top of the PTB that enables researchers to write readable, clean, and concise code. In addition to presenting the architecture of the o_ptb, the results of a timing accuracy test are presented. Exactly the same MATLAB code was run on two different systems, one of those using the VPixx system. Both systems showed sub-millisecond accuracy.